2018
DOI: 10.3389/fpsyg.2018.01534
|View full text |Cite
|
Sign up to set email alerts
|

Large-Group One-Session Treatment: A Feasibility Study of Exposure Combined With Applied Tension or Diaphragmatic Breathing in Highly Blood-Injury-Injection Fearful Individuals

Abstract: Objective: Large-group one-session treatments (LG-OSTs) might represent a promising treatment tool as increasing evidence suggests their effectiveness in individuals with different situational fears. In the present study, we explored feasibility and effectiveness of an exposure-based LG-OST protocol applying applied tension and diaphragmatic breathing as coping strategies in a sample of 40 individuals, highly fearful of blood-injury-injection (BII).Method: We assessed participants’ BII-fear using questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
1
9
2
Order By: Relevance
“…Our successful translation of individual to large group OST using direct exposure is consistent with Wannemueller et al's (, , ) studies, which found that exposure tasks modelled to large groups ( N = 40+) was effective in reducing fear, demonstrating that various formats of OST (direct or indirect exposure) are adaptable to large group delivery. While the group size in the current study may be considered modest compared to Wannemueller et al's studies (in which exposure to the feared stimuli was observational), they are the largest group size evaluated for treatments involving direct exposure and interaction with the feared stimuli (twice the size of Öst et al's (, 1997) original group evaluations).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our successful translation of individual to large group OST using direct exposure is consistent with Wannemueller et al's (, , ) studies, which found that exposure tasks modelled to large groups ( N = 40+) was effective in reducing fear, demonstrating that various formats of OST (direct or indirect exposure) are adaptable to large group delivery. While the group size in the current study may be considered modest compared to Wannemueller et al's studies (in which exposure to the feared stimuli was observational), they are the largest group size evaluated for treatments involving direct exposure and interaction with the feared stimuli (twice the size of Öst et al's (, 1997) original group evaluations).…”
Section: Discussionsupporting
confidence: 87%
“…They found exposure tasks modelled to a large group was as effective as the same exposure tasks modelled to an individual. Using a similar indirect (i.e., observational) exposure procedure Wannemueller and colleagues further demonstrated the benefit of large group OST by showing moderate to large effects of large group OST in reducing self‐reported phobic‐relevant fear in high dental fearful ( N = 24) and high blood–injection–injury fearful ( N = 40) individuals (Wannemueller et al, ; Wannemueller et al, ). However, there are no investigations into the feasibility and effectiveness of OST delivered to groups larger than eight (termed here large group OST) when using direct exposure, or when delivered to a sample of individuals meeting diagnostic criteria for spider phobia.…”
mentioning
confidence: 99%
“…Prior LG-OST trials suggest large-group exposure might represent promising treatment alternatives for situational fears, and proved especially promising in spider fear and blood-injury-injection fear (Wannemueller et al, 2016, 2018). Results of the present study provide further evidence for the suggestion also in terms of treating severe FoH.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the weaknesses mentioned, we conclude that an LG-OST targeting height-fear represents a very valuable treatment tool. Prior experience with LG-OSTs in spider-fear blood injury injection-fear and dental fear (Wannemueller et al, 2016, 2017, 2018) suggest that LG-OST might represent useful options either as a single treatment or as a step within a stepped care model of SP treatment. The size and stability of effects we observed here suggest that in case of FoH, the LG-OST protocol may sufficiently address the treatment needs of most participants – especially those who report good positive mental health indices prior treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation